The Politicization of Religion on Facebook Social Media in Elections Governor of North Sumatra in 2018 - Muhammad Akhyar Hasibuan; Katimin Katimin; Anang Anas Azhar (LPPPIPublishing, 2022)
This study examines the politicization of religion through social media Facebook that occurred during the election campaign for the Governor and Deputy Governor of North Sumatra from January to June 2018. This was followed by two pairs of candidates, namely Eramas and Djoss. There are three research questions posed: 1) How is the politicization of religion on Facebook social media in the 2018 North Sumatra gubernatorial election, 2) How is the candidate pair politicizing religion through Facebook social media, 3) the relationship between the politicization of religion and Facebook social media. By using qualitative research methods the researchers traced and collected data through in-depth interviews, as well as observation and documentation. The results of this study reveal that: first, the construction of issues that link religious issues in the 2018 North Sumatra gubernatorial election is interactive. Where there are two or more Facebook users who are involved in the interaction of exchanging messages and the role as communicators and interacting communicants are in full control of the timing, content, actions of communication and the text to be disseminated. Second, departing from the public opinion that was built, each candidate in the 2018 North Sumatra gubernatorial election, both the Eramas couple and the Djoss pair used buzzers in their campaign activities. In further battles, there was a crystallization of issues that linked everything related to religion on Facebook. Third, the game of religious symbols cannot be separated from the hope of gaining support from a specific mass base. The construction of these symbols is deliberately presented to inspire potential voters with the form of pride and fanaticism of religion, ethnicity, and race on social media Facebook